PRONOMINA PERSONA BAHASA MELAYU RIAU DIALEK RANAI - Ma’rifatul Hidayati; Mangatur Sinaga; Auzar Auzar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThis study discusses pronouns Riau dialect of Malay persona Ranai, namely the shape and use of pronomin Riau dialect of Malay persona Ranai. This research uses descriptive qualitative research method that aims to describe the shape and use of pronouns Riau dialect of Malay persona Ranai. Subjects of this study 10 men, 4 women and 6 men. This study uses data types of oral and written. Data sourced from oral language users Ranai Malay dialect and writing of data derived from folklore who are in Natuna regency Ranai City. Data obtained from engineering records and record then classified based on shape and using it, and formulated into a knot. Based on data analysis and the use of pronouns form persona Riau Malay Dialect Ranai. Forms of pronouns Riau dialect of Malay persona Ranai consists of singular and plural and inclusive, exclusive and neutral. The use of pronouns Riau dialect of Malay persona Ranai based on three parameters: age, social status and familiarity.Keywords: pronouns persona, designanduse